Uncovering the social impacts of Facebook on a college campus - Vanden Boogart, Matthew Robert (Kansas State University, 2006)
With the creation of Facebook in 2004, colleges and universities across the United States have been playing catch-up with students. This new technology carries much weight as a new medium for students to build social connections and grow as members of their institutions. However, this new technology also brings negative implications such as lowered GPAs with greater use. Research was conducted at four major institutions across the country exploring how residence hall students use online communities and the impact it has on their physical world experience on campus. Most students use Facebook as a tool for staying connected to friends from high school, but there is a small population of students who are using it as a tool to make social connections they could not find in person. This study explores the impacts Facebook has had on a college campus. University administrators are urged to use this data to take a proactive approach to using these technologies to enhance the overall campus experience.
Keywords: Facebook; Online communities; Residence halls; Social networks; Dormitory; Education, Higher (0745)